Education Planning Curriculum Based on Technology: Impact Evaluation - Yuliza, Yuliza (Islamic Educational Management Programme, 2022)
Curriculum planning is the initial stage of an element of management. The curriculum is an important part of the educational process. Education without a curriculum will look disorganized. In addition, the curriculum is a medium for achieving educational goals, and at the same time, also serves as a guide for the implementation of the teaching and learning process in various types and levels of educational units. Curriculum planning is a central function of learning management and must be future-oriented. In this regard, this article aims to examine how technology-based curriculum planning. Based on the author's analysis, educational curriculum planning in each educational system must be adapted to the needs of society and the times. Therefore, curriculum planning must change over time. all curriculum planning processes cannot be separated from the problem of change, such as a revolution in methods, a revolution in a more innovative curriculum, technology, and critical Human Resources (HR) to produce creativity and work results as a form of change for the better. Educational institutions must have a future orientation following the needs of the times so that students can have global competitiveness.